Randomized clinical trial of brief risk reduction counseling for sexually transmitted infection clinic patients in Cape Town, South Africa. - Kalichman, Seth C; Cain, Demetria; Eaton, Lisa; Jooste, Sean; Simbayi, Leickness C (American journal of public health, 2011)
We examined the effects of a brief counseling intervention designed to reduce HIV risk behaviors and sexually transmitted infections (STIs) among patients receiving STI services in Cape Town, South Africa.
Keywords: Adult; Alcohol Drinking; Ambulatory Care Facilities; Counseling; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Male; Motivation; Patient Education as Topic; Risk Reduction Behavior; Self Efficacy; Sex Factors; Sexual Behavior; Sexually Transmitted Diseases; Socioeconomic Factors; South Africa